Effect of papain on the kinetics of llama sperm (Lama glama) - Cucho, Hernán (2020)
The aim of this study was to determine the effect of papain treatment on the kinetics of llama sperm. Four 5-8-year-old Ch'aku male llamas were selected and semen was collected using an artificial vagina and a dummy. Four semen collections were made per animal with intervals of one week. The semen samples were separated into two aliquots. One for fresh analysis and the other to be treated with papain (20 minutes). The volume, filancia, concentration of sperm, percentage of live sperm, percentage of functionality of the sperm membrane, and percentage of sperm with acrosomal reaction were evaluated. Sperm mobility and its kinetics were evaluated using a CASA-Mot system (ISAS®), determining the total motility (MT) and progressive motility (MP), as well as the sperm kinetic parameters: curvilinear velocity (VCL), straight-line velocity (VSL), average path velocity (VAP), and the indices of straightness (STR), linearity (LIN) and wobble (WOB), the amplitude of lateral head movement (ALH) and beat cross frequency (BCF). The effect of papain was analysed with a random block factorial model. MT did not show significant differences between fresh and degelified semen with papain, but MP was higher with papain (p<0.05). Greater values (p<0.05) were found in papain-degelled semen in relation to fresh semen for VCL, VSL, VAP, LIN, STR and BCF, which suggests that treatment with papain improves progressive motility, as well as most of the kinetic parameters of llama sperm.